Enhanced angiotensin-mediated excitation of renal sympathetic nerve activity within the paraventricular nucleus of anesthetized rats with heart failure - Zheng, Hong (American Physiological Society, 2009)
Chronic heart failure (HF) is characterized by increased sympathetic drive. Enhanced angiotensin II (ANG II) activity may contribute to the increased sympathoexcitation under HF condition. The present study examined sympathoexcitation by 1) the effects of ANG II in the paraventricular nucleus (PVN) on renal sympathetic nerve activity (RSNA), and 2) the altered ANG II type 1 (AT(1)) receptor expression during HF. Left coronary artery ligation was used to induce HF. In the anesthetized Sprague-Dawley rats, microinjection of ANG II (0.05–1 nmol) into the PVN increased RSNA, mean arterial pressure (MAP), and heart rate (HR) in both sham-operated and HF rats. The responses of RSNA and HR were significantly enhanced in rats with HF compared with sham rats (RSNA: 64 ± 8% vs. 33 ± 4%, P < 0.05). Microinjection of AT(1) receptor antagonist losartan into the PVN produced a decrease of RSNA, MAP, and HR in both sham and HF rats. The RSNA and HR responses to losartan in HF rats were significantly greater (RSNA: −25 ± 4% vs. −13 ± 1%, P < 0.05). Using RT-PCR and Western blot analysis, we found that there were significant increases in the AT(1) receptor mRNA (Δ186 ± 39%) and protein levels (Δ88 ± 20%) in the PVN of rats with HF (P < 0.05). The immunofluorescence of AT(1) receptors was significantly higher in the PVN of rats with HF. These data support the conclusion that an increased angiotensinergic activity on sympathetic regulation, due to the upregulation of ANG II AT(1) receptors within the PVN, may contribute to the elevated sympathoexcitation that is observed during HF.